2006
DOI: 10.1002/adfm.200400528
|View full text |Cite
|
Sign up to set email alerts
|

Local Probing of Photocurrent and Photoluminescence in a Phase‐Separated Conjugated‐Polymer Blend by Means of Near‐Field Excitation

Abstract: In this paper scanning near‐field microscopy is used to characterize polymer blends for photovoltaic applications, and fluorescence imaging and photoconductivity are combined to elucidate the spatial distribution and relative efficiency of current generation and photoluminescence in different domains of compositionally heterogeneous films. Focus is placed on a binary system consisting of poly[(9,9‐dioctylfluorene)‐alt‐benzothiadiazole] (F8BT) and poly[(9,9‐dioctylfluorene)‐alt‐(bis(N,N′‐(4‐butylphenyl))‐bis(N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…It was ascertained that they were mixed domains due to photocurrent from both the phases. Riehn et al studied the PFB:F8BT system by p-NSOM and concluded that regions rich in PFB had a certain F8BT concentration and vice versa [88]. The current contribution from the PFB rich domains was about four times that of an F8BT region confirming that the donor absorption was responsible for the majority of charge carrier generation.…”
Section: Transparent Electrode Geometrymentioning
confidence: 88%
See 1 more Smart Citation
“…It was ascertained that they were mixed domains due to photocurrent from both the phases. Riehn et al studied the PFB:F8BT system by p-NSOM and concluded that regions rich in PFB had a certain F8BT concentration and vice versa [88]. The current contribution from the PFB rich domains was about four times that of an F8BT region confirming that the donor absorption was responsible for the majority of charge carrier generation.…”
Section: Transparent Electrode Geometrymentioning
confidence: 88%
“…However, effects of light interaction with a metal layer or tip are generally not considered in the image analysis. Although, Riehn et al had solved the Poisson equation with a commercial finite element package in order to arrive at perturbation effects of a metalized nearfield at the vicinity of a photoconductive material [88].…”
Section: Transparent Electrode Geometrymentioning
confidence: 99%
“…Near-field scanning optical microscopy (NSOM) has also been successively applied to characterise conjugated polymers [21][22][23] and organic BH solar cells. [24][25][26][27] This specific scanning probe method is based on a tip probe in which an optical fibre is embedded to locally illuminate the sample. This allows local characterisation of photoconductive properties and raises therefore significant interest in the field of organic photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state NMR spectroscopy and relaxometry are powerful non-invasive and non-destructive techniques to investigate the segmental chain dynamics and the molecular miscibility of polymer blends and copolymers at the nanoscale. [24][25][26][27] This specific scanning probe method is based on a tip probe in which an optical fibre is embedded to locally illuminate the sample. This allows local characterisation of photoconductive properties and raises therefore significant interest in the field of organic photovoltaics.…”
mentioning
confidence: 99%
See 1 more Smart Citation